The crustal structure of Onega-Kandalaksha paleorift identified by complex analysis of the anomalous magnetic field of the White Sea - A. S. Baluev; Yu. V. Brusilovsky; A. N. Ivanenko (Геодинамика и тектонофизика, 2018)
Geological and geophysical studies recently conducted in the White Sea and the adjacent territory have provided new data on the deep structure of this region. Our study aims to conduct complex analysis of the anomalous magnetic field and the geological and geophysical data on the Onega-Kandalaksha paleorift located in the White Sea basin and the adjacent southeastern land area, and to develop a model showing its deep structure. The basis for analysing the magnetic field is the anomalous magnetic field (AMF) map constructed by the authors using the magnetic survey data consolidated by the Marine Arctic Geological Expedition (MAGE) in 2003–2008 and supplemented by the survey data of the Institute of Oceanology RAS in 2001–2004. The parameters of the magnetically active layer are estimated by the independent complementary methods of quantitative interpretation developed by the Laboratory of Geophysical Fields, P.P. Shirshov Institute of Oceanology RAS. This article describes a model showing the structure and formation of the magnetically active layer of the White Sea paleorift. Our study shows that the magnetically active layer of the paleorift system has a complex structure reflecting all the main stages in the evolution of tectonic activity in the White Sea region, from the Middle and Late Riphean to the last glaciation of the Quaternary period. The model includes three structural layers, each corresponding to a certain stage. The bottom structural layer is the base of the magnetically active layer, which reflects the continental rifting stage in the evolution of the White Sea mobile belt in the Middle and Late Riphean. The middle structural layer reflects the Middle Paleozoic (Late Devonian) stage of rifting reactivation, which is characterized by alkaline-ultrabasic magmatism and represented by swarms of alkaline dykes and diatremes, including kimberlite pipes. The top structural layer reflecting a high-frequency component of the AMF is related to the highly magnetic sources of anomalies located in the upper part of this structural layer. The characteristics of the top structural layer suggest that it formed in the Late Pleistocene – Holocene and developed during the final stage the tectonic activation of this region. The deep crustal structure of the White Sea basin is specified in our model showing the magnetically active layer for the low-frequency component of the AMF. In the southeastern part of the basin, magmatism products of the basic (Riphean – Vendian) and alkaline-ultrabasic (Middle Paleozoic) composition are abundant in the crust and provide for a strong magnetic source of anomalies, the lower edges of which are traced at the depths to 30 km. This probably reflects the most active plume-lithospheric interaction. Wedging and uplifting of the magnetically active layer northwestward along the Onega-Kandalaksha rift is related to the White Sea (Belomorsky) deep fault. This fault is a long-lived conduit that channels magma from the central portion of the plume, as evidenced by the igneous bodies of the basic composition in the basement and central parts of the sedimentary wedge in the Kandalaksha graben. The complex analysis of the AMF in the White Sea region suggests the presence of morphologically different igneous bodies in the upper crust in the study region.